Evaluation of Efficacy and Safety of Oral Olmesartan+ Chlorthalidone Combination in the Management of Hypertension in Indian Patients (Journal of Medicine, 2017)
Hypertension is the most prevalent chronic disease in India and its prevalence is rapidly increasing among urban and rural populations. Reducing blood pressure can decrease cardiovascular risk and all cause mortality. This study was conducted to assess the efficacy and safety of fixed dose combination of Olmesartan 40 mg and Chlorthalidone12.5mg. 30 hypertensive patients having systolic blood pressure ? 160 mmHg and diastolic blood pressure ?100 mmHg who were uncontrolled on monotherapy with olmesartan were enrolled in this study. The treatment period was of 60 days and patients were administered once daily fixed dose combination of Olmesartan40 mg and Chlorthalidone 12.5 mg. Patients were evaluated on 15th, 30th and 60th days of treatment.There was statistically significant (p